2016
DOI: 10.1097/ccm.0000000000001472
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Acute Kidney Injury–Induced Neutrophil Dysfunction: A Critical Role for Resistin*

Abstract: Objectives To assess the reversibility of acute kidney injury (AKI)-induced neutrophil dysfunction and to identify involved mechanisms. Design Controlled laboratory experiment and prospective observational clinical study. Setting University laboratory and hospital. Subjects C57BL/6 wild-type mice. Patients Patients with septic shock with or without AKI. Interventions Murine AKI was induced by i.p. injections of folic acid (nephrotoxic AKI) or by i.m. injections of glycerol (rhabdomyolysis-induced AKI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 39 publications
5
63
0
1
Order By: Relevance
“…Furthermore, there is lack of reliable data on the time course of the failing organs. Where RRT is initiated, incidences of respiratory failure between 23 and 44% have been reported with several pathophysiological mechanisms implicated in the development of ARDS (ESM Table 7). A study of > 7 million individuals with acute ischaemic stroke showed that the need for IMV was significantly GRADE system for grading recommendations according to strength of recommendation (strong vs. weak) and quality of evidence (high to very low) Modified from Guyatt et al [8] higher among patients with AKI than in those without (3.6% vs. 0.7%; p < 0.0001) [9].…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is lack of reliable data on the time course of the failing organs. Where RRT is initiated, incidences of respiratory failure between 23 and 44% have been reported with several pathophysiological mechanisms implicated in the development of ARDS (ESM Table 7). A study of > 7 million individuals with acute ischaemic stroke showed that the need for IMV was significantly GRADE system for grading recommendations according to strength of recommendation (strong vs. weak) and quality of evidence (high to very low) Modified from Guyatt et al [8] higher among patients with AKI than in those without (3.6% vs. 0.7%; p < 0.0001) [9].…”
Section: Rationalementioning
confidence: 99%
“…Notably, not all AKI models demonstrate consistent pulmonary involvement with some suggesting that AKI only worsens pre-existing pneumonia by reducing signalling in neutrophils (e.g. the phosphatidylinositol 3-kinase-γ pathway) leading to impaired formation and localization of F-actin (essential for neutrophil movement), reduced pulmonary neutrophil recruitment and transmigration [19,23,24].…”
Section: Rationalementioning
confidence: 99%
“…Our group and others have demonstrated that CytoSorb effectively extracts serum resistin, an early-phase 12.5 kDa inflammatory cytokine associated with increased sepsis severity, impaired neutrophil migration, and intracellular bacterial clearance [22,23,95,96]. Furthermore, this therapy reverses neutrophil dysfunction DOI: 10.1159/000492379 and restores their bacterial killing function, suggesting a direct benefit to the innate immune system [22].…”
Section: Literature Evidence For Cytokine Adsorption Therapymentioning
confidence: 99%
“…Specifically, elevated serum IL-6 and resistin levels appear to correlate with sepsis severity and end-organ damage [23]. By extension, serum levels of key anti-inflammatory cytokines such as IL-10, as well as PAMPs and DAMPs also appear to predict outcomes, presumably due to poor regulation of the proinflammatory response [19].…”
Section: The Cytokine Storm and Sepsismentioning
confidence: 99%
“…B. Migration und Bakterienelimination, hemmt und so zur Verschlechterung einer Pneumonie beitragen kann [41]. Auf diese Weise lassen sich auch die erhöhten Raten an Pneumonien und mediastinalen Infektionen bei postherzchirurgischer AKI erklären [42][43][44][45].…”
Section: » Eine Aki Hemmt Grundlegende Funktionen Der Neutrophilen Grunclassified